FTIR, a powerful technique in organic coatings failure diagnosis - Costa, M. Rosário (2012)
FTIR spectrometry (Fourier Transform Infrared) is an instrumental technique of analysis that presents significant advantages on the dispersive traditional system, such as the increase of the relation signal-noise, the capacity of getting absorption spectra of low energy and therefore, bands of absorption of weak intensity. This technique is widely used in the study of resin characterization and evaluation of polymeric materials as well as degradation when polymers and coatings are exposed to various conditions of service, or still in the analysis and diagnosis of defects that occur during the application or production process. Techniques connected to the FTIR have appeared such as the photoacoustic (PAS-FTIR), the microscopy (MCT-FTIR) and the attenuated total reflectance (ATR), which allows to analysis of weekly transparent and dark samples without removal of coatings from the substrates. The choice of the technique to use depends on the morphology of the surfaces to analyze and the type of failure (lack of adhesion, contamination, aging degradation, etc). This work illustrates the application of FTIR and associated techniques to identify causes of diverse types of defects in applied organic coatings on polymeric materials.